The Effectiveness of a Training Program for the Development of Social Interaction and Reduction of some Behavioral Problems among Autistic Students Skills at the Primary area Tabuk, Saudi Arabia - Rania E. A. Abdel Kawi (Sultan Qaboos University, 2016)
The study aimed at designing a training program for social skills in reducing some behavioral problems among a sample of female autistic students from Saudi Arabia. The sample consisted of 24 student wih an age range 7-14 years, and IQ between 55 and 68. The researcher used several tools including: Intelligence scale, socio-economic status, and the training program. The sample was devided into two groups: experimental and control. The main results of the study showed that there were differences between the mean scores of the experimental and control groups in telemetric problems of behavioral and social skills in favor of the experimental group. Also there were differences between the mean scores of the pre-test and post-test of experimental group in regard to the behavioral problems and social skills. However, there was no significant difference between the post-test and the extended effect (2 months afte the end of the program) whether in behavioral problems or social skills.